Factors Influencing Medication Adherence and Blood Pressure Control in Hypertensive Outpatients - Rahmah Inasiyyah; Silma Kaaffah; Fauziah Fauziah (International Journal Labs, 2026)
Hypertension is a leading cause of premature mortality worldwide and remains a major challenge in healthcare, as it requires long-term therapy with sustained treatment adherence. Therapeutic success is strongly influenced by patients’ regularity in medication use, yet adherence often poses a clinical barrier. This study aimed to analyze the influence of demographic, clinical, and lifestyle factors on medication adherence and blood pressure control among hypertensive outpatients at Prof. Dr. Margono Soekarjo Hospital. A cross-sectional design was employed using primary and secondary data collected from March to June 2025. A total of 369 respondents were recruited through purposive sampling. Most participants were ?60 years (71%), female (54.2%), highly educated (63.7%), married (93%), unemployed (55.6%), and had comorbidities (84%). Overall, 80.5% of respondents were adherent to medication, while 62.1% achieved controlled blood pressure, consisting of 22.3% aged <60 years with <140/90 mmHg and 77.7% aged ?60 years with <150/90 mmHg. Bivariate analysis revealed that the clinical factor of Body Mass Index (BMI) (p=0.004) and the lifestyle factor of alcohol consumption (p=0.039) significantly influenced treatment adherence. Furthermore, demographic factor of age (p=0.026), clinical factor of BMI (p=0.004), and lifestyle factor of physical exercise (p=0.017) were significantly associated with blood pressure control. In conclusion, most hypertensive outpatients were adherent to therapy, but blood pressure control remained suboptimal. Clinical factors (BMI) and lifestyle factors (alcohol consumption) significantly influenced adherence, whereas demographic (age), clinical (BMI), and lifestyle (exercise) factors significantly influenced blood pressure control.